A scoping review protocol on knowledge, perceptions and attitudes toward cervical cancer among Ghanaians - Isaac Aidoo Erzuah; Christiana Asiedu; Amidu Alhassan; Ernest Addae (Discover Public Health, 2026)
Abstract Introduction Cervical malignancy remains a major public health challenge in low- and middle-income countries, with sub-Saharan Africa bearing a disproportionate burden of disease. In Ghana, cervical cancer incidence and mortality remain high despite the availability of effective preventive measures, including human papillomavirus (HPV) vaccination and screening. Knowledge, perceptions, and attitudes influence uptake of cervical cancer prevention services, yet evidence from Ghana remains limited. This scoping review aims to map and synthesize available evidence on knowledge, perceptions, and attitudes toward cervical cancer among Ghanaians. Methods and analysis The review will follow the methodological framework outlined by Arksey and O’Malley, enhanced by the Joanna Briggs Institute guidelines for scoping reviews, which will help to strengthen the methodological rigor of the review. A literature search will be undertaken in PubMed, Scopus, Web of Science, CINAHL, ScienceDirect, and African Journals Online (AJOL). Studies published in English between January 2016 and January 2026 will be eligible for inclusion. Search terms: ‘Cervical cancer’, ‘knowledge’, ‘attitudes’, ‘perceptions’, ‘Ghana’ and related syntax will be used to identify literature. Two reviewers will independently screen titles, abstracts, and full texts, with disagreements resolved through consensus. The Preferred Reporting Items for Systematic Reviews and Meta Analyses extension for Scoping Reviews will be used to report the results of this study. Ethics and dissemination Ethical approval is not required for this review, as it will use publicly available data. Findings will be disseminated through peer-reviewed publications, conference presentations, and stakeholder engagement to inform cervical cancer prevention strategies and support progress toward the World Health Organization’s cervical cancer elimination targets in Ghana.